STRATEGI MANAJEMEN DALAM PENGUATAN BUDAYA BELAJAR BERKELANJUTAN PADA ORGANISASI MAHASISWA: STUDI PADA HMI KOMISARIAT TARBIYAH UIN RADEN INTAN LAMPUNG - Nasyiruddin Firdaus; Oki Dermawan; Iqbal Iqbal (Jurnal Manajemen Pendidikan, 2025)
Objective: This study aims to analyze the POAC-based management strategy (Planning, Organizing, Actuating, Controlling) in strengthening the continuous learning culture within the Islamic Students Association (HMI) Komisariat Tarbiyah at UIN Raden Intan Lampung. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that although each POAC function has been implemented, its execution remains suboptimal. In the planning aspect, the organization has established intellectual-oriented training programs; however, they are not fully supported by needs analysis and risk-based planning. The organizing aspect shows a structurally well-defined system, yet coordination among divisions is still weak. In the actuating aspect, participatory leadership has been applied, but member participation remains inconsistent and heavily influenced by individual motivation. Regarding the controlling aspect, evaluation mechanisms are not well documented, resulting in repetitive issues and the absence of structured recommendations. This study concludes that the POAC management strategy has substantial potential to strengthen a sustainable learning culture, but requires improvement in coordination, program implementation discipline, member motivation, and systematic evaluation mechanisms.